2017
DOI: 10.22616/foodbalt.2017.041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraction conditions on phenolic compounds from blackberry leaves extracts

Abstract: Blackberry leaves have been used as a tea substituent in many herbal mixtures. Medicinal properties of this plant material are related to a high level of components with antioxidant activity, such as phenolic compounds. The aim of the research was to evaluate the effect of different extraction conditions on the content of phenolic compounds and antioxidant activity of blackberry leaves extracts. In this study, blackberry leaves extracts were produced by an aqueous extraction procedure. Different extraction con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The highest TFC was observed in blueberries with 70.31 ± 1.21 µg QE/g and the lowest in strawberries with 14.31 ± 0.13 µg QE/g. In previous studies, the TFC value were 30.44–91.69 mg QE/100 mg in blueberries [ 36 ], blackberries leaves with 449.00–715.00 mg QE/L based on their extraction temperature ranging between 40–80 °C [ 37 ], strawberries with 14.6 ± 3.0 mg QE/100 g [ 38 ] and raspberries 73.70–51.14 mg QE/100 g f.w. [ 39 ] which showed almost similar values to our study.…”
Section: Resultsmentioning
confidence: 99%
“…The highest TFC was observed in blueberries with 70.31 ± 1.21 µg QE/g and the lowest in strawberries with 14.31 ± 0.13 µg QE/g. In previous studies, the TFC value were 30.44–91.69 mg QE/100 mg in blueberries [ 36 ], blackberries leaves with 449.00–715.00 mg QE/L based on their extraction temperature ranging between 40–80 °C [ 37 ], strawberries with 14.6 ± 3.0 mg QE/100 g [ 38 ] and raspberries 73.70–51.14 mg QE/100 g f.w. [ 39 ] which showed almost similar values to our study.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of DPPH is followed by a decrease in its absorbance. According to the previously described procedure ( 14 ), an aliquot of each sample (0.2 mL) was mixed with 2.8 mL of DPPH ethanolic solution (Sigma-Aldrich Chemie, Merck, Steinheim, Germany). Ethanol (Vrenje Spiritana, Belgrade, Serbia) was used as a blank, while ethanol with DPPH solution was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Foods are being extensively tested to obtain additional health benefits that reduce the risk of chronic diseases and improve health, so nowadays, the challenge is no longer limited to production only. Studies reported that the leaves and roots of blackberry plants are used to treat several diseases, and many studies referred to the importance of the plant in lowering blood sugar in diabetic persons [2,3]. There is an increasing global demand towards searching for healthy food regimens.…”
Section: Introductionmentioning
confidence: 99%